2002
DOI: 10.1590/s0100-40422002000200007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização textural e estrutural de V2O5/TiO2 obtidos via sol-gel: comparação entre secagem convencional e supercrítica

Abstract: . This work describes a modified sol-gel method for the preparation of V 2 O 5 /TiO 2 catalysts. The samples have been characterized by N 2 adsorption at 77K, x-ray diffractometry (XRD) and Fourier Transform Infrared (FT-IR). The surface area increases with the vanadia loading from 24 m 2 g Embora vários estudos tenham mostrado que atividade catalítica da vanadia suportada sobre TiO 2 anatásio é superior quando suportada sobre TiO 2 rutilo, outros autores mostraram que não existe diferença de atividade entre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…The presence of adsorbed water increases the degree of disorder and affects the stretching vibration of V=O species, thus shifting the vibrations towards a lower wavenumber (Rodella et al 2002). The presence of silver in the system also affects the metal-oxygen vibrational mode thus contributing to the band shift compared with the spectrum of ammonium vanadate.…”
Section: Characterizationsmentioning
confidence: 99%
“…The presence of adsorbed water increases the degree of disorder and affects the stretching vibration of V=O species, thus shifting the vibrations towards a lower wavenumber (Rodella et al 2002). The presence of silver in the system also affects the metal-oxygen vibrational mode thus contributing to the band shift compared with the spectrum of ammonium vanadate.…”
Section: Characterizationsmentioning
confidence: 99%
“…The technique for the synthesis of aerogels occurs in supercritical conditions and was created by Kistler, 1 with the goal of producing a dry gel with superior physical properties and the same volume of moist gel as other methods, replacing the solvent in gas pores. 2 Aerogels based on silica and other metal oxides are extremely porous, with high specific surface areas and low density. Studies have shown the use of aerogels for lipase encapsulation by the sol-gel technique, as the enzyme is physically encapsulated in a rigid glass framework that permits stabilisation of the enzymes and gives a tertiary structure because of the tight gel network.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior may be explained by Ti-O bond breakage in the presence of vanadium. [24]. Ionic radius difference between V 5+ (0.58 Å ) and Ti 4+ (0.68 Å ) may lead to a crystallographic adjustment which promotes a surface area increase, specially for low vanadium loadings, which do not affect titania pore volume.…”
Section: Characterizationmentioning
confidence: 99%